Effect of substrate dispersion method and particle size on in vitro digestibility, gas production kinetics and composition, and fermentation characteristics in different feed types - Sousa, Luiz C. O.; Matos, Ellem M. A.; Trotta, Ronald J.; Detmann, Edenio; Harmon, David L. (Frontiers in Animal Science, 2026)
Our objective was to evaluate the influence of substrate dispersion method and particle size on in vitro digestibility, gas production kinetics and composition, and fermentation characteristics of different feed types. Alfalfa hay, tall fescue hay, ground corn, soybean meal, and a total mixed ration (TMR) were used as substrates. Treatments were designed according to a 2 × 2 × 5 factorial arrangement: two substrate dispersion methods (loose substrate and in filter bags), two particle sizes (1 mm and 2 mm), and five feeds. Filter bags decreased (P ≤ 0.001) digestibility and gas production compared with loose samples. Filter bags decreased digestibility and total gas production to a greater extent for forages, whereas the effects on concentrate feeds were less pronounced. Using filter bags decreased (P ≤ 0.015) both methane production and methane concentration in headspace gas across all feeds. Substrates incubated in filter bags showed a lower molar proportion of acetate and a greater molar proportion of propionate than loose substrates (P< 0.001). In general, energy-rich feeds incubated using filter bags had a decreased (P ≤ 0.036) acetate-to-propionate ratio, while substrate dispersion method did not influence (P ≥ 0.16) the VFA profile of protein-rich feeds. Incubating substrates in filter bags alters in vitro digestibility, gas production, and fermentation characteristics regardless of particle size. However, the magnitude of responses is greater for forage-based feeds than concentrate feeds.